The Use of Obesity Indicators for the Prediction of Hypertension Risk among Youth in the United Arab Emirates - SS Al-Sharbatti; RB Shaikh; E Mathew; Jayadevan Sreedharan; J Muttappallymyalil; SA Basha (Tehran University of Medical Sciences, 2011)
Background: Obesity is a significant risk factor for metabolic disorders including increase in blood pressure. Body mass index (BMI), waist circumference (WC) and Waist/Hip ratio (WHR) are simple and effective indicators of obesity. The objectives of this study were to examine the relationships between obesity anthropometric indicators and hypertension and to identify the best anthropometric indicator/s that can predict hypertension risk among youth in the UAE. Methods: A 110 first year students in a Medical University in Ajman, UAE, during the year 2009-2010 were included in a cross-sectional study. The height, weight, WC, hip circumference and blood pressure were measured and the BMI and WHR were calculated for each student and used in the analyses. Results: The mean values for BMI, WC, hip circumference and WHR, were significantly higher in the Pre/Hypertensive group compared to normal blood pressure group. The risk of Pre/ hypertension was significantly increased by 4.3 times for participants who had general obesity (BMI³ 30) or abdominal obesity (identified from high WC). Highly significant correlations were noticed between systolic and diastolic blood pressure and all anthropometric indicators except that for Hip circumference and systolic blood pressure. Step-wise linear regression model showed that when all obesity indicators were studied together, the waist circumference was the only indicator which showed significant relationship with both systolic and diastolic blood pressure. Conclusion: Waist circumference is the best anthropometric indicator that can predict hypertension risk among youth in the UAE.